Proteomic screening of plasma identifies potential noninvasive biomarkers associated with significant/advanced fibrosis in patients with nonalcoholic fatty liver disease. Issue 1 (3rd January 2020) - Hou, Wei; Janech, Michael G.; Sobolesky, Philip M.; Bland, Alison M.; Samsuddin, Salma; Alazawi, William; Syn, Wing-Kin
Abstract: Noninvasive biomarkers are clinically useful for evaluating liver fibrosis stage in patients with nonalcoholic fatty liver disease (NAFLD). The aim of the present study was to compare plasma proteins in patients with early nonalcoholic steatohepatitis (NASH) (F0-F1) versus NASH with significant/advanced fibrosis (F2–F4) to determine whether candidate proteins could be used as potential noninvasive biomarkers. Nineteen biopsy-proven NAFLD patients including ten early NASH patients and nine NASH patients with significant/advanced fibrosis were enrolled in the present study. High-resolution proteomics screening of plasma was performed with the SCIEX TripleTOF 5600 System. Proteins were quantified using two different software platforms, Progenesis Qi and Scaffold Q+, respectively. Progenesis Qi analysis resulted in the discovery of 277 proteins compared with 235 proteins in Scaffold Q+. Five consensus proteins (i.e. Complement component C7; α-2-macroglobulin; Complement component C8 γ chain; Fibulin-1; α-1-antichymotrypsin) were identified. Complement component C7 was three-fold higher in the NASH group with significant/advanced fibrosis (F2–F4) compared with the early NASH (F0-F1) group (q-value = 3.6E-6). Complement component C7 and Fibulin-1 are positively correlated with liver stiffness ( P =0.000, P =0.002, respectively); whereas, Complement component C8 γ chain is negatively correlated ( P =0.009). High levels of Complement C7 are associated with NASH with significant/advanced fibrosis and Complement C7 is a perfect classifier of patients included in this pilot study. Further studies will be needed in a larger validation cohort to confirm the utility of complement proteins as biomarkers or mechanistic determinants of NASH with significant/advanced fibrosis.